Cholinergic Interneurons Amplify Corticostriatal Synaptic Responses in the Q175 Model of Huntington’s Disease - Tanimura, Asami; Lim, Sean Austin O.; Aceves Buendia, Jose de Jesus; Goldberg, Joshua A.; Surmeier, D. James (Frontiers in Systems Neuroscience, 2016)
Huntington’s disease (HD) is a neurodegenerative disorder characterized by deficits in movement control that are widely viewed as stemming from pathophysiological changes in the striatum. Giant, aspiny cholinergic interneurons (ChIs) are key elements in the striatal circuitry controlling movement, but whether their physiological properties are intact in the HD brain is unclear. To address this issue, the synaptic properties of ChIs were examined using optogenetic approaches in the Q175 mouse model of HD. In ex vivo brain slices, synaptic facilitation at thalamostriatal synapses onto ChIs was reduced in Q175 mice. The alteration in thalamostriatal transmission was paralleled by an increased response to optogenetic stimulation of cortical axons, enabling these inputs to more readily induce burst-pause patterns of activity in ChIs. This adaptation was dependent upon amplification of cortically evoked responses by a post-synaptic upregulation of voltage-dependent Na+ channels. This upregulation also led to an increased ability of somatic spikes to invade ChI dendrites. However, there was not an alteration in the basal pacemaking rate of ChIs, possibly due to increased availability of Kv4 channels. Thus, there is a functional ‘re-wiring’ of the striatal networks in Q175 mice, which results in greater cortical control of phasic ChI activity, which is widely thought to shape the impact of salient stimuli on striatal action selection.